(3TQM GdMce GdYWGFjIs - (3GdTjN GdWjHs; (3eMeO haG GdTGPdj , eMeO Hf eMeO Hf eMeO GdScfOQj, CHh GdaVd (B- (3CHh GdaJM,J (B765 (3g` s
(3ChdgG (B:s
(3bhdg djchf gPG EbGeI GdUdGI s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG hehdGfG eMeO NGJe GdfHjjf hEeGe GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdfUa GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B37 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B279s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B675s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs